MOVEMENT ANALYSIS OF LONG JUMP SKILLS - Gammal A Nasser; Iman Sulaiman; Aan Wasan (Gladi : Jurnal Ilmu Keolahragaan, 2021)
Socialization regarding technical motion analysis using technological tools. It is also possible that in analyzing technical motions, they only use the sense of sight, namely the eyes in the process of analyzing students' technical movements. This feels less than optimal because the eyes have limitations. This study aims to analyze the performance of jumping skills which includes four factors, namely prefix, repulsion, hovering in the air and landing and whether there is a step shortening distance before taking off. This research is a type of qualitative descriptive research. The results of the data obtained are then analyzed using the Dartfish Prosuite software. This research will be carried out in the field of Plus Pembangunan Jaya Senior High School, South Tangerang City. As for the subjects in this study, 17 students aged 15-17 years. The results of the analysis of the motion of long jump skills at Plus Pembangunan Jaya Senior High School, South Tangerang City which includes four factors, namely prefix, repulsion, hovering in the air and landing. fit into the "suitable" criteria. Based on the results of the analysis, no one has shortened the steps before taking off on students at Plus Pembangunan Jaya Senior High School, South Tangerang City. It is known that the athlete's initial running speed every 8 meters has increased with an average speed of 7.2m/s.